Repeatedly heating cooking oil among food premise operators in Bukit Mertajam, Pulau Pinang and determination of peroxide in cooking oil - Abdul Aziz, Adriana; Mohd Elias, Saliza; Sabran, Mohd Redzwan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: The repeatedly heating cooking oil in preparation of fried food has become a main dietary habit among Malaysian which can cause health impacts on humans. The peroxide value (PV) can be applied to identify cooking oil’s quality through the oxidative change that takes place in fats or oils. High peroxide value indicates bad quality of cooking oil. This research was conducted to identify the awareness and practice of repeatedly heating cooking oil among food premise operators and to determine the peroxide value in repeatedly heating cooking oil samples. Methods: A total of 124 food premise operators in Bukit Mertajam, Penang, participated in this research. A face-to-face interview was carried out by using the structured questionnaire for data collection to obtain socio-demographics information as well as awareness and practice of repeatedly heating cooking oil among respondents. The peroxide values analysis was performed on five samples of respondent’s most favourable brands of cooking oil by using iodometric titration method. Results: Majority of respondents had moderate awareness (53.2%) and practice (50.0%) level regarding repeatedly heating cooking oil. The PV analysis showed that the peroxide value begin to exceed the AOCS standard limit of 10 meqO2/kg following the 5th cycles of frying. Conclusion: Relevant actions need to be taken by the governmental food authorities to address this issue and ensure safe consumption of fried foods by consumers.